Acquired Myelodysplasia or Myelodysplastic Syndrome: Clearing the Fog - Ethan A. Natelson; David Pyatt (Advances in Hematology)
Myelodysplastic syndromes (MDS) are clonal myeloid disorders characterized by progressive peripheral blood cytopenias associated with ineffective myelopoiesis. They are typically considered neoplasms because of frequent genetic aberrations and patient-limited survival with progression to acute myeloid leukemia (AML) or death related to the consequences of bone marrow failure including infection, hemorrhage, and iron overload. A progression to AML has always been recognized among the myeloproliferative disorders (MPD) but occurs only rarely among those with essential thrombocythemia (ET). Yet, the World Health Organization (WHO) has chosen to apply the designation myeloproliferative neoplasms (MPN), for all MPD but has not similarly recommended that all MDS become the myelodysplastic neoplasms (MDN). This apparent dichotomy may reflect the extremely diverse nature of MDS. Moreover, the term MDS is occasionally inappropriately applied to hematologic disorders associated with acquired morphologic myelodysplastic features which may rather represent potentially reversible hematological responses to immune-mediated factors, nutritional deficiency states, and disordered myelopoietic responses to various pharmaceutical, herbal, or other potentially myelotoxic compounds. We emphasize the clinical settings, and the histopathologic features, of such AMD that should trigger a search for a reversible underlying condition that may be nonneoplastic and not MDS.